Development of Conceptual Flexibility in Intuitive Biology: Effects of Environment and Experience - Betz, Nicole; Coley, John D. (Frontiers in Psychology, 2020)
Living things can be classified by taxonomic similarity (lions and lynx), or shared ecological habitat (ducks and turtles). The present studies used card-sorting and triad tasks to explore developmental and experiential changes in conceptual flexibility–the ability to switch between taxonomic and ecological construals of living things–as well as two processes underlying conceptual flexibility: salience (i.e., the ease with which relations come to mind outside of contextual influences) and availability (i.e., the presence of relations in one’s mental space) of taxonomic and ecological relations. We were also interested in the extent to which salience and availability of taxonomic and ecological relations predicted inductive inferences. Participants were 452 six to ten-year-olds from urban, suburban, and rural communities in New England. Across two studies, taxonomic relations were overwhelmingly more salient than ecological relations, although salience of ecological relations was higher among children from rural environments (Study 1) and those who engaged in unstructured exploration of nature (Study 2). Availability of ecological relations, as well as conceptual flexibility, increased with age, and was higher among children living in more rural environments. Notably, salience, but not availability, of ecological relations predicted ecological inferences. These findings suggest that taxonomic relations are a default way to organize intuitive biological knowledge and that environmental richness and relevant experience contribute to the salience and availability of ecological knowledge, and thereby, conceptual flexibility in biological thinking. More generally, they highlight important linkages between domain-specific knowledge and domain-general cognitive abilities.